Main COVID-19 information sources in a culturally and linguistically diverse community in Sydney, Australia: A cross-sectional survey. Issue 8 (August 2022) - Ayre, J.; Muscat, D.M.; Mac, O.; Batcup, C.; Cvejic, E.; Pickles, K.; Dolan, H.; Bonner, C.; Mouwad, D.; Zachariah, D.; Turalic, U.; Santalucia, Y.; et al.
Abstract: Objective: Describe COVID-19 information-seeking experiences for culturally and linguistically diverse groups in Sydney, Australia. Methods: Cross-sectional survey, translated into 11 languages; participants recruited from March 21 to July 9, 2021. Regression models identified factors associated with difficulty finding easy-to-understand COVID-19 information. Results: Across 708 participants (88% born overseas, 31% poor English proficiency), difficulty finding easy-to-understand COVID-19 information was rated 4.13 for English (95%CI: 3.85–4.41) and 4.36 for non-English language materials (95%CI: 4.07–4.66) (1 easy to 10 hard). Participants who were older (p < 0.001), had inadequate health literacy (p < 0.001), or poor English proficiency (p < 0.001) found it harder to find easy-to-understand English-language COVID-19 information. Those who had greater difficulty finding easy-to-understand non-English COVID-19 information were younger (p = 0.004), had poor English proficiency (p < 0.001), were university-educated (p = 0.05), and had spent longer living in Australia (p = 0.001). They were more likely to rely on friends and family for COVID-19 information (p = 0.02). There was significant variation in information-seeking experiences across language groups (p's < 0.001). Conclusions: Easy-to-understand and accessible COVID-19 information is needed to meet the needs of people in culturally and linguistically diverse communities. Practice implications: COVID-19 communication efforts must involve working alongside these communities to leverage existing communication channels and tailor messages. Highlights: COVID-19 experience survey 708 people from 11 language groups in Sydney, Australia. English COVID-19 information less accessible for older people with low health literacy. Substantial differences in information-seeking experiences across language groups. People with low health literacy relied more on friends/family and overseas sources. COVID-19 communication efforts must be tailored for culturally diverse communities.